2018
DOI: 10.2495/ei-v1-n2-172-182
|View full text |Cite
|
Sign up to set email alerts
|

Risk of asthma symptoms among workers in health care settings

Abstract: Prevalence of asthma is quite high in health care settings due to exposure to a wide variety of substances, including cleaning products, latex, medicines, ammonia and solvents. In this cross-sectional study, participants completed a validated questionnaire about their occupation, asthma diagnosis, variability of asthma symptoms at and away from work, and exposure to individual substances in the workplace. Work-related asthma symptoms (WRAS) were defined based on a set of criteria. Principal component analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
1
1
Order By: Relevance
“…Furthermore, in this current study, lifetime prevalence of work‐related ocular–nasal (23%) and asthma symptoms (12%) was higher than that reported in South African dental HWs (14% and 4%, respectively) 34 . Moreover, in this current study, the prevalence of work‐related asthma symptoms (WRAS) in the past 12 months (7%) was higher than that reported in a US study of HWs (3.3%) and on the upper end of the range compared to the Saudi Arabian study of HWs (5.7%), both using a similar definition of WRAS 48,49 . Although the authors did not comment on the adequacy of workplace control measures in the two studies, 48,49 the inadequate controls observed in the current study (manuscript under review; unreferenced) could partly explain the relatively higher prevalence of WRAS.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, in this current study, lifetime prevalence of work‐related ocular–nasal (23%) and asthma symptoms (12%) was higher than that reported in South African dental HWs (14% and 4%, respectively) 34 . Moreover, in this current study, the prevalence of work‐related asthma symptoms (WRAS) in the past 12 months (7%) was higher than that reported in a US study of HWs (3.3%) and on the upper end of the range compared to the Saudi Arabian study of HWs (5.7%), both using a similar definition of WRAS 48,49 . Although the authors did not comment on the adequacy of workplace control measures in the two studies, 48,49 the inadequate controls observed in the current study (manuscript under review; unreferenced) could partly explain the relatively higher prevalence of WRAS.…”
Section: Discussioncontrasting
confidence: 73%
“…34 Moreover, in this current study, the prevalence of work-related asthma symptoms (WRAS) in the past 12 months (7%) was higher than that reported in a US study of HWs (3.3%) and on the upper end of the range compared to the Saudi Arabian study of HWs (5.7%), both using a similar definition of WRAS. 48,49 Although the authors did not comment on the adequacy of workplace control measures in the two studies, 48,49 the inadequate controls observed in the current study (manuscript under review; unreferenced) could partly explain the relatively higher prevalence of WRAS. Furthermore, 16 (2%) workers with WRAS in the current study had to change their jobs due to these symptoms, underscoring the negative consequences associated with continued exposure for work-related asthma.…”
Section: Discussionmentioning
confidence: 81%